2005
DOI: 10.1074/jbc.m410148200
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor (FGF) 18 Signals through FGF Receptor 3 to Promote Chondrogenesis

Abstract: Signaling by fibroblast growth factor (FGF) 18 and FGF receptor 3 (FGFR3) have been shown to regulate proliferation, differentiation, and matrix production of articular and growth plate chondrocytes in vivo and in vitro. Notably, the congenital absence of either FGF18 or FGFR3 resulted in similar expansion of the growth plates of fetal mice and the addition of FGF18 to human articular chondrocytes in culture enhanced proliferation and matrix production. Based on these and other experiments it has been proposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
183
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 224 publications
(200 citation statements)
references
References 49 publications
12
183
0
2
Order By: Relevance
“…In contrast, the expression of FGFR1 in hypertrophic chondrocytes suggests a role for FGFR1 in regulating cell survival, cell differentiation, ECM production and cell death (Peters et al, 1992). Recently, findings from our laboratory and others suggest that FGF-18 signals selectively through FGFR3 in human articular chondrocytes and mice to suppress cellular proliferation and promote limb mesenchymal cell differentiation (Davidson et al, 2005;Muddasani et al, 2008), as opposed to bFGF-FGFR1 binding that characterizes increased proliferation and catabolic effects seen in articular and IVD cartilage (Figure 3).…”
Section: (B) Extracellular Signaling Mediated By Fgf-18mentioning
confidence: 94%
See 1 more Smart Citation
“…In contrast, the expression of FGFR1 in hypertrophic chondrocytes suggests a role for FGFR1 in regulating cell survival, cell differentiation, ECM production and cell death (Peters et al, 1992). Recently, findings from our laboratory and others suggest that FGF-18 signals selectively through FGFR3 in human articular chondrocytes and mice to suppress cellular proliferation and promote limb mesenchymal cell differentiation (Davidson et al, 2005;Muddasani et al, 2008), as opposed to bFGF-FGFR1 binding that characterizes increased proliferation and catabolic effects seen in articular and IVD cartilage (Figure 3).…”
Section: (B) Extracellular Signaling Mediated By Fgf-18mentioning
confidence: 94%
“…In contrast to the controversial role of bFGF in joint and spine disc cartilage, FGF-18 is a well-known anabolic growth factor involved in osteogenesis, chondrogenesis, and articular cartilage repair (Ellsworth et al, 2002;Liu et al, 2002;Ohbayashi et al, 2002;Davidson et al, 2005;Moore et al, 2005), and here we will review its role in joint cartilage. To date, the role of FGF-18 in the IVD has yet to be studied.…”
Section: Introductionmentioning
confidence: 99%
“…2 Fibroblast growth factor receptor 3 (FGFR3) has been shown to inhibit chondrocyte proliferation, with FGF18 possibly the important ligand in growth cartilage. 3,4 Endochondral ossification is blocked in Runx2-deficient mice, indicating an essential role for this transcription factor in chondrocyte differentiation. It has been shown that expression of Runx2 induces hypertrophy, alkaline phosphatase activity, and expression of type X collagen and matrix metalloproteinase-13 (MMP-13) 5 in chondrocytes, as well as mineralization of the cartilage matrix.…”
mentioning
confidence: 99%
“…However, cells that were not precultured had higher wet mass and collagen type II mRNA levels at 3 weeks. It is known well that MSC proliferation is downregulated once differentiation is initiated [35,36]. The decreased proliferation rate of precultured hPDMSCs may therefore be due to increased chondrogenesis.…”
Section: Discussionmentioning
confidence: 99%